(untitled) (Research, Society and Development, 2021)
The Covid-19 pandemic is recognized by the WHO as an international public health emergency, which reveals several aspects of health, pathogenesis, epidemiology and care. The most susceptible populations include elderly people regardless of their health status, among others, the importance of understanding the role of nursing in the context of elderly health is highlighted. The objective of this paper is to discuss the impact of the global pandemic on the health of the elderly and the need for professional intervention to maintain quality of life. The search for studies was carried out in the NCBI/PubMed, SciELO, Academic Google and Lilacs - Bireme databases. To delimit the contents, inclusion criteria were used: articles available in full, in Portuguese and English, from 2019 to 2021 with free access and that were relevant to the theme. From the analysis of the nine articles, it was shown that the elderly face more threats and challenges in face of reality, as the physiological changes caused by the aging process directly affect their immune function and possible underlying health conditions. In addition, temporal factors and typical pathologies such as dementia, stroke and fractures, the elderly have increased their susceptibility to infection and embolism, which is related to the current infection caused by the pandemic. It was concluded that nurses are essential for promoting the health of the elderly, and carrying out actions to raise awareness of the elderly, as the impacts of the pandemic affect them in several aspects.